Uveitis as an ophthalmologic manifestation of autoimmune diseases: A detailed analysis of the clinical implications (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
Uveitis, an ocular condition characterized by inflammation of the middle layer of the eye, can manifest itself in association with various systemic diseases, with autoimmune diseases being a prominent component. Its complexity lies in its etiological diversity and the variety of clinical manifestations, ranging from mild to severe presentations. The aim of this research is to analyze the prevalence and characteristics of uveitis in the context of autoimmune diseases, and to examine the associated clinical repercussions. A comprehensive literature review was conducted using specialized databases, the sample comprised epidemiological studies and systematic reviews related to AD and associated rheumatic diseases. The results revealed a significant prevalence of uveitis in patients with AS, highlighting the importance of ophthalmologic surveillance in this population.